Conservation challenges of sharks with continental scale migrations - Heupel, Michelle R.; Simpfendorfer, Colin A.; Espinoza, Mario; Smoothey, Amy F.; Tobin, Andrew; Peddemors, Victor (Frontiers in Marine Science, 2015)
Understanding movement and connectivity of populations is increasingly important as human and climate change pressures become more pervasive, but can be problematic in difficult to observe species such as large marine predators. We examined the movements of bull sharks, Carcharhinus leucas, using acoustic telemetry arrays along the east coast of Australia. Approximately half of 75 individuals released in temperate waters moved into tropical reef regions, with both sexes undertaking long-range movements and multiple individuals making return trips. Only 3% of 39 individuals released in tropical reef habitats moved south to temperate waters, but approximately 25% moved to southern reef or subtropical coastal areas. These results reveal complex linkages along the east coast of Australia which suggest a tropical reef based population comprised of individuals that migrate to multiple regions. Connectivity between locations along the east coast of Australia creates important conservation challenges for resource managers in multiple jurisdictions.